Hydrodynamic performances of FPSO and shuttle tanker during side-by-side offloading operation. (3rd October 2019) - Xu, Xiaosen; Sahoo, Prasanta; Evans, Johanna; Tao, Yanwu
ABSTRACT: The Floating Production Storage and Offloading (FPSO) unit are one of the most popular approaches to exploiting petroleum and natural gas. During the offloading operation, the responses of FPSO and shuttle tanker become complicated because of the hydrodynamic interactions. This paper presents a comprehensive study on the coupling effects on hydrodynamic characteristics of FPSO and shuttle tanker during side-by-side offloading in both frequency and time domain. During the transfer operation, the draft of FPSO and shuttle tanker would change accordingly, resulting in the change of hydrodynamic characteristics and pose a potential threat. Added mass and quadratic transfer function (QTF) are calculated in different working condition and incident angles in the frequency domain. Time domain analysis is based on the spread mooring and side-by-side offloading system. Power spectral densities and statistical characteristics of hawsers' tensions are calculated to determine the most hazardous environmental condition.